Improving Students’ Concept with POE2WE Learning Model Assisted by PhET Android Simulation - Deo Demonta Panggabean; Grace Dita Maria Naibaho; Ika Trisni Simangunsong (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to determine the influence of the POE2WE learning model assisted by the Android Lab Virtual PhET application on students' understanding of the Equilibrium of Rigid Objects. The type used in this study was quasi-experiment with research subjects of SMA Negeri 2 Medan students class XI MIPA 7 as an experimental class and XI MIPA 8 as a control class. The data analysis technique used is quantitative. The results of the research obtained were the influence of the POE2WE learning model assisted by the Android Lab Virtual PhET application on students' understanding of concepts on the equilibrium material of rigid objects in the medium category with an n-Gain test of 58.6%. Based on the results of the study, the application of the POE2WE learning model assisted by the PhET virtual android lab application can increase students' understanding of concepts on the equilibrium rigid body material.